2018
DOI: 10.1016/j.amjcard.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes for Off-Pump Versus On-Pump Coronary Artery Bypass Grafting in Low-Volume and High-Volume Centers and by Low-Volume and High-Volume Surgeons

Abstract: In terms of in-hospital outcomes, controversy still remains whether off-pump coronary artery bypass grafting is superior to on-pump coronary artery bypass surgery. We investigated whether the volume of off-pump coronary artery bypass procedures by hospital and individual surgeon influences patient outcomes when compared with on-pump coronary artery bypass surgery. Discharge records from the Nationwide Inpatient Sample were retrospectively reviewed for in-hospital admissions from 2003 to 2011, including 999 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…Conversely, in high-volume OPCAB centers (≥ 164 cases/year) and surgeons (≥ 48 cases/year), OPCAB reduced mortality compared with on-pump CABG in cases requiring a single graft or two or more grafts. Therefore, OPCAB outcome is dependent on volume at both the institution and the individual surgeon levels and should not be performed at low-volume centers and by low-volume surgeons [9] .…”
Section: Experience As a Determinant Of Results - The Role Of Expertisementioning
confidence: 99%
“…Conversely, in high-volume OPCAB centers (≥ 164 cases/year) and surgeons (≥ 48 cases/year), OPCAB reduced mortality compared with on-pump CABG in cases requiring a single graft or two or more grafts. Therefore, OPCAB outcome is dependent on volume at both the institution and the individual surgeon levels and should not be performed at low-volume centers and by low-volume surgeons [9] .…”
Section: Experience As a Determinant Of Results - The Role Of Expertisementioning
confidence: 99%
“…Um estudo realizado por Benedetto et al (16), envolvendo 999 centros de cirurgia cardíaca e um total de 2.094.094 pacientes, comparou os resultados de CRM com e sem CEC procurando evidenciar diferenças nos desfechos dos procedimentos realizados por cirurgiões que possuíam uma maior experiência no procedimento sem bomba versus cirurgiões que eram menos experientes nessa técnica, bem como os resultados de centros que realizavam com maior e menor frequência o procedimento sem CEC. O grupo concluiu que, para procedimentos sem CEC, os resultados são claramente dependentes do volume cirúrgico, tanto do centro de cirurgia cardíaca como do cirurgião individual (14). Esse estudo é de grande relevância, pois infere que, os resultados pós-operatórios da CRM sem CEC estão intimamente relacionados com a acurácia do cirurgião, sendo que serão positivos, se realizados por uma equipe experimente neste procedimento.…”
Section: Discussionunclassified
“…Another potential advantage of using multiple arterial grafts is the possibility to perform off-pump CABG (OPCABG) without manipulation of the ascending aorta (an-aortic OPCABG). This has been shown to reduce the risk of stroke by 78% when compared to conventional on-pump CABG [34] . However, this is arguably the most technically challenging variant of CABG and an analysis of registry data from the US showed that OPCABG has better in-hospital results compared to on-pump surgery for large volume centers and surgeons but worse outcomes when compared to conventional on-pump CABG in low volume settings [35] .…”
Section: The Case For Subspecialization In Surgical Myocardial Revascularizationmentioning
confidence: 99%